Alternative Solutions to Increase Pension Security Participation in Indonesia - Meutia, Astrid; Hamzah, Muhammad Zilal; Rumondang, Haiyani (Green Publisher Indonesia, 2024)
This study aims to analyze alternative solutions to increase the number of pension security participation in Indonesia. The analysis method used in this study is Panel Data Regression. The data used in the panel data analysis are Number of Pension Security Participants, Human Development Index (HDI), Gross Regional Domestic Product (GRDP), Open Unemployment Rate (TPT), Information and Communication Technology Development Index (IPTIK), Young age (15-24) who are not in school, working or training (NEET), Proportion of Average Hourly Wages to Provincial Minimum Wage (Wages), Gini Ratio, Labor Force Participation Rate (TPAK) from 2017-2022 in 33 Provinces in Indonesia. The results of panel data processing, the best model is the Fixed Effect Model with regression results showing that only GRDP variables have a significant positive influence. While the Wage variable has a significant negative effect and the IPM, TPT, IPTIK, NEET, Gini Ratio, TPAK variables have no influence on the Number of Pension Security Participants.